The Effectiveness of The Open-Ended Learning Model in Improving Students' Mathematical Problem-Solving Ability - Hana Kamilah; Charis Maulana (International Journal of Ethno-Sciences and Education Research, 2026)
This study examines the effectiveness of the open-ended learning model in improving the mathematical problem-solving ability of ninth-grade students at SMA Muhammadiyah 1 Semarang. A quasi-experimental, nonequivalent control-group design was used, employing parametric statistical analysis. The research population consisted of ninth-grade students at the school, from which two classes were selected through cluster random sampling: Class IX-A as the experimental group, instructed using the open-ended learning model, and Class IX-C as the control group, instructed using conventional teaching. Mathematical problem-solving ability was measured with a five-item essay test. Hypothesis testing using an independent-samples t-test produced t = 9.57, which exceeds the critical value t-table = 2.00 at the 5% significance level, indicating a statistically significant difference between the two groups. It can therefore be concluded that there is a significant effect of applying the open-ended learning model on students' mathematical problem-solving ability in Class IX of SMA Muhammadiyah 1 Semarang during the 2024/2025 academic year. This conclusion is reinforced by the considerable gap between the experimental group's mean score (75.00) and the control group's mean score (41.20). These findings support the theoretical proposition that instructional approaches emphasizing multiple solution strategies and student-centered inquiry cultivate deeper mathematical reasoning than approaches built around a single, teacher-demonstrated procedure.